Regional Economic Outlook, May 2005 : Sub-Saharan Africa. (Regional Economic Outlook, 2006)
The five Regional Economic Outlooks published biannually by the IMF cover Asia and Pacific, Europe, the Middle East and Central Asia, Sub-Saharan Africa, and the Western Hemisphere. In each volume, recent economic developments and prospects for the region are discussed as a whole, as well as for specific countries. The reports include key data for countries in the region. Each report focuses on policy developments that have affected economic performance in the region, and discusses key challenges faced by policymakers. The near-term outlook, key risks, and their related policy challenges are analyzed throughout the reports, and current issues are explored, such as when and how to withdraw public interventions in financial systems globally while maintaining a still-fragile economic recovery.These indispensable surveys are the product of comprehensive intradepartmental reviews of economic developments that draw primarily on information the IMF staff gathers through consultation with member countries.